Comparison of the prevalence and molecular characteristics of fosA3 and fosA7 among Salmonella isolates from food animals in China. (17th March 2022) - Wang, Dong; Fang, Liang-Xing; Jiang, Yu-Wei; Wu, De-Shu; Jiang, Qi; Sun, Ruan-Yang; Wang, Min-Ge; Sun, Jian; Liu, Ya-Hong; Liao, Xiao-Ping
Abstract: Objectives: To investigate the prevalence and molecular characteristics of fosA3 and fosA7 among Salmonella isolates. Methods: Five hundred and fifty-one Salmonella isolates collected from food animals in China during 2016–19 were screened for fos genes. The drug resistance, serovars, clonal relationships and genetic environments of fosA were compared between fosA7- and fosA3 -positive Salmonella . Results: A relatively high prevalence of fosA7 (9.26%) and fosA3 (6.53%) was identified. fosA3 was associated with high-level fosfomycin resistance (≥512 mg/L), while fosA7 conferred relatively low-level resistance that was independent of the presence of glucose-6-phosphate. Additionally, fosA7 could facilitate Salmonella survival under oxidative stress. Both fosA3 and fosA7 were found in diverse serovars and STs, but segregated into distinct groups. The fosA3 -positive Salmonella Typhimurium/ Salmonella Indiana strains showed close genetic relationships, while fosA7 -positive Salmonella Meleagridis/ Salmonella Agona/ Salmonella Derby showed a relatively high degree of whole-genome sequence heterogeneity. fosA3 was located on conjugative IncHI2 plasmids or chromosomes, while fosA7 was strictly chromosomal. Furthermore, two strains carried large chromosomal fosA7 regions within genomic islands. The fosA3 and fosA7 contigs from our isolates and the NCBI could be segregated into four primary and distinct genomic backbones. IS 26 and the antibiotic resistance genes (ARGs) bla CTX-M, bla TEM-1B and rmtB were frequently adjacent to fosA3, while fosA7 -carrying contigs generally lacked mobile elements and ARGs. Conclusions: fosA3 and fosA7 were the primary factors contributing to reduced fosfomycin susceptibility, to different degrees, in these Salmonella isolates. The distinct distributions and molecular characteristics of fosA7 and fosA3 indicated that their origin and evolution in Salmonella were most likely distinct.